Rising Indian Clinical Trials Industry and Career Opportunities - Biswas, Arghya (Journal of Applied Pharmaceutical Research, 2021)
The Indian clinical trials industry has seen stable growth over the past decades and especially since 2014 there has been a significant rise. With the current expected market growth rate, India has the potential to become one of the largest clinical trial hubs. The ministry of health had a very positive outlook towards the growth of the Indian clinical trial market; with the constant reformation of the regulatory guidance, the confidence of pharma companies to do trials in India is growing. The Covid-19 pandemic has caused mass public awareness about clinical trials and drug development process, this will increase acceptance and help to further promote the industry. This article provides an insight into the various drivers for the fast growth of the Indian clinical trials industry and at the same time discusses the numerous career opportunities the industry offers.